Analysis of Sharia Bank Service Management in the New Normal Period in Terms of Empathy and Responsiveness Dimensions - Pratama, Ariski; Wulandari, Nina Ramadhani; Mawardi, Mawardi (widya balina, 2023)
This service management is a crucial process as it can prevent various service-related issues when serving customers. This study aims to understand how the Service Management of Islamic Banks in the New Normal era is perceived in terms of the dimensions of Empathy and Responsiveness. In this research, a qualitative method with a case study approach was employed. Data collection techniques included observation, interviews, and documentation. The research results indicate that in terms of Service Management at the bank, there have been changes in the dimension of Empathy. For example, in welcoming customers, before the existence of the coronavirus, employees greeted customers without wearing masks, there were no barriers or partitions, and their facial expressions were visible. In the new normal, employees must wear masks, there are barriers between customers and employees, and customers cannot discern the facial expressions of employees, whether they are smiling or not. This can lead to customer uncertainty about whether the employee is serving sincerely or not. As for the dimension of Responsiveness, significant changes are evident in customer queues. Before the coronavirus, customer queues could be quite long, whereas during the pandemic, customer queues are limited, and the service takes longer than before. The speed of service is also constrained.